2021
DOI: 10.1002/chem.202100655
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Activation of Aromatic Aldehydes: Synthesis of Amides, Hydroxamic Acids and Esters

Abstract: A cheap, facile and metal-free photochemical protocol for the activation of aromatic aldehydes has been developed. Utilizing thioxanthen-9-one as the photocatalyst and cheap household lamps as the light source, a variety of aromatic aldehydes have been activated and subsequently converted in a one-pot reaction into amides, hydroxamic acids and esters in good to high yields. The applicability of this method was highlighted in the synthesis of Moclobemide, a drug against depression and social anxiety. Extended a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 124 publications
2
21
0
Order By: Relevance
“…Phenyl(pyrrolidin‐1‐yl)methanone (5 b) : [49] Yield 600 mg (96 %) from 5 a (253 mg, 3.56 mmol). Colorless liquid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenyl(pyrrolidin‐1‐yl)methanone (5 b) : [49] Yield 600 mg (96 %) from 5 a (253 mg, 3.56 mmol). Colorless liquid.…”
Section: Methodsmentioning
confidence: 99%
“…19 13 C NMR (126 MHz, CDCl 3 ): δ = 170.7, 132.4, 131.6, 128.7, 127.9, 126.2 (q, J = 275.5 Hz), 52.5, 48.4, 32.6 ppm (q, J = 32.3 Hz). 19 [49] Yield 600 mg (96 %) from 5 a (253 mg, 3.56 mmol). Colorless liquid.…”
Section: N-(444-trifluorobutyl)benzamide (3 B{γ3}mentioning
confidence: 99%
“…A diversity of various secondary cyclic amines, including pyrrolidine, piperidine, azepane, morpholine, thiomorpholine and piperazine, were also explored, generating amides 8ag–8ak in 83–96% yields. Amidation of pyrrolidine gave the amide 8ag in a much higher yield of 90% than the reported yields of 33% and 38% obtained with the thioxanthen-9-one photocatalyst 20 and monometallic Ln[N(SiMe 3 ) 2 ] 3 complexes. 10 a The bis-amidation of piperazine resulted in 94% yield under the optimal conditions (Table 3, 8al ).…”
Section: Resultsmentioning
confidence: 63%
“…During the preparation of this review, Kokotos and coworkers reported the use of thioxanthone as the photocatalyst for the generation of acyl radicals from aromatic aldehydes. 101 This acyl radical was trapped by N-chlorosuccinimide, leading to the corresponding acyl chloride, which is subsequently reacted with amine, a hydroxyamine or an alcohol leading to an amide, a hydroxamic acid or an ester, respectively. Aliphatic aldehydes could not be employed.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%